Epithelioid hemangioendothelioma: an overview and update on a rare vascular tumor - Angela Sardaro (Oncology Reviews, 2014)
Epithelioid hemangioendothelioma is a rare vascular tumor, described for the first time in 1975 by Dail and Liebow as an aggressive bronchoalveolar cell carcinoma. The etiology is still a dilemma. Studies about suggestive hypothesis are ongoing. Most of the times it affects lung, liver and bones, although this kind of tumor may involve the head and neck area, breast, lymph nodes, mediastinum, brain and meninges, the spine, skin, abdomen and many other sites. Because of its heterogeneous presentation, as it represents less than 1% of all the vascular tumors, it is often misdiagnosed and not suitably treated, leading to a poor prognosis in some cases. Over 50-76% of the patients are asymptomatic. A small number of them complains respiratory symptoms. Bone metastases might cause pathological fractures or spine compression, if they arise in vertebrae. Imaging is necessary to determine morphological data, the involvement of surrounding tissues, and potentially the cleavage plan. It is important to recognize the expression of vascular markers (Fli-1 and CD31 are endothelial-specific markers), and the microscopic evidence of vascular differentiation to make a correct diagnosis, as many pulmonary diseases show multiple nodular lesions. Because of its rarity, there is no standard for treatment. We focused on radiotherapy as a good therapeutic option: despite the poor prognosis, evidence is in favor of radiotherapy which offers local pain control with good tolerance and better quality of life at least at a one-year follow-up in most of cases. Further studies are needed to establish the standard radiation dose to be used for locoregional control of such a complex and extremely rare disease.